Quantum cryptography with bright entangled beams - Leuchs, Gerd; et al. (IQEC'2000 Conference Digest, 2000)
A scheme for the generation of bright entangled beams is discussed. The Einstein-Podolsky-Rosen (EPR) quantum correlations are produced by letting two amplitude-squeezed bright optical fields interfere on a 50:50 beamsplitter. This is illustrated in the phase space representation in a single-mode picture. The phase and amplitude uncertainty measurements exhibit strong correlations and anticorrelations which can be detected by recording the difference of the photocurrents.
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.quantu_2